Embedding Biomaterials into Mortars for Enhancement of Some Physical-Mechanical Properties - Carla-Cezarina Pădurețu; Mihaela-Luminița Udrea; Madalina Elena David; Rodica-Mariana Ion (Proceedings, 2020)
The history portrays the identity of a culture, of people and various civilizations, which has [...]